Case report of rib polyostotic fibrous dysplasia - Mohamed Magdy Abd Elalim; Amr Abdou Ettish; Wael Mohamed Elfeky; Mohamed Moustafa Abdelaal (Journal of the Pakistan Medical Association, 2023)
Polyostotic fibrous dysplasia is a rare benign asymptomatic tumour of the ribs not requiring surgery on most occasions. We present here a case with left 10th and 11th rib fibrous dysplasia which was causing a hinderance to the Urologist for renal stone extraction. Therefore the 10th and 11th ribs were excised followed by chest wall reconstruction. Keywords: Fibrous dysplasia, polyostotic, thoracic wall, ribs, neoplasms